Visual evoked potentials in overt hypothyroid patients before and after achievement of euthyroidism - Aprajita; Geetanjali Sharma; Sameer Aggarwal (Indian Journal of Endocrinology and Metabolism, 2017)
Background: Visual evoked potential (VEP) measures the time taken for visual stimulus to travel from the eye to the occipital cortex. Hypothyroidism affects the central nervous system (CNS) through its role in gene expression, myelin production, axonal transportation, and neurotransmitters. Delay in the conduction of impulses results in abnormal VEP. Objective: Correlate the electrophysiological findings of VEP in newly diagnosed treatment-naive hypothyroid patients before and after 3 months of treatment and to find the correlation with serum thyroid-stimulating hormone (TSH) levels. Materials and Methods: VEP was measured using Recorders and Medicare Systems Electromyograph Evoked Potential Mark II machine in 30 patients (serum TSH ≥10 mIU/L) between 18 and 50 years of age who were followed up after 3 months of treatment. Results: The mean age (±standard deviation) of the patients was 31.8 (±8.3) years. There was prolongation of VEP latencies which tends to decrease following hormone replacement therapy. It was found to be most significant for P100 (ms) waveform (P < 0.001). The amplitude (P100-N75 mV) which was decreased in hypothyroid patients showed improvement following achievement of euthyroidism. Significant positive correlation was found between P100, N75 latency and pretreatment serum TSH levels. Conclusion: Hypothyroid patients may have changes in the latencies and the amplitude of VEP which are reversible to a great extent with thyroxine replacement therapy. VEP thus acts as a dependable marker for CNS affection in thyroid diseases to detect subtle early changes and to assess the response to treatment in correlation with the clinical improvement.